Implementasi Thermoelectric Generator Lilin Sebagai Solusi Energi Tepat Guna Daerah Terpencil Kalimantan - isdhianto, Irfan; Himawan, Helmy Mukti; Setiawan , Dona (Politeknik Negeri Malang, 2025)
The demand for electricity in remote areas of Kalimantan remains a significant challenge due to the limited reach of the national power grid. This research aims to develop a low cost, eco friendly, and practical power generation solution using a thermoelectric generator (TEG) integrated with a candle based heat source. A prototype candle tube was designed and constructed using copper heat exchangers, TEG modules, and passive cooling systems (heatsinks). The system was tested under two conditions using one and two candles as heat sources while powering LED lights. Temperature data on the hot and cold sides of the TEG were recorded using an Arduino data logger, and the electrical output (voltage and current) was monitored using a USB multimeter. Results showed that increasing the number of candles significantly raised the temperature difference across the TEG, from 24°C with one candle to 39°C with two, leading to a voltage increase from 2.68 V to 2.80 V, current from 0.06 A to 0.16 A, and power output from 0.15 W to 0.44 W. These findings demonstrate that the system's performance correlates directly with the thermal gradient. With its simple design, accessible materials, and passive operation, this candle based TEG system offers a promising alternative energy source for rural communities lacking access to conventional electricity, especially in Kalimantan’s interior regions.